2020
DOI: 10.1021/acsomega.0c02084
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Relative Dielectric Constant and the Monomer Sequence of Acrylonitrile in Rubber

Abstract: Acrylonitrile-butadiene rubbers (NBRs) have a lower glass transition temperature (T g) and a higher dielectric constant than other rubbers. To understand how a low T g and a high dielectric constant are compatible, we focused on the acrylonitrile (AN) monomer sequence in rubber and synthesized random and alternating copolymers to evaluate the effect of the sequence. The AN monomer sequence dependence of the relative dielectric constant was investigated by the C–N stretching vibration of the nitrile group throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Consistent with our present findings, Wang et al (2017) also reported that materials with high moisture exhibits greater capacitance due to high dielectric constant of water (ε r = 80). NBR at 100Hz have a dielectric constant of 10 or more at room temperature (Matsuno et al, 2021). During drying process, water diffuses and dries off from glove surface, causing drastic drop in gloves dielectric constant.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with our present findings, Wang et al (2017) also reported that materials with high moisture exhibits greater capacitance due to high dielectric constant of water (ε r = 80). NBR at 100Hz have a dielectric constant of 10 or more at room temperature (Matsuno et al, 2021). During drying process, water diffuses and dries off from glove surface, causing drastic drop in gloves dielectric constant.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with our present findings, Wang et al (2017) also reported that materials with high moisture exhibits greater capacitance due to high dielectric constant of water (εr = 80). NBR at 100Hz have a dielectric constant of 10 or more at room temperature (Matsuno et al, 2021). During drying process, water diffuses and dries off from glove surface, causing drastic drop in gloves dielectric constant.…”
Section: Resultsmentioning
confidence: 99%
“…An elastomer having flexibility and a high dielectric constant is needed. In our previous research, we reported that HXNBR exhibited a high dielectric constant (14) and flexibility . Additionally, Poikelispää et al reported the high actuation performance of NBR rubbers .…”
Section: Introductionmentioning
confidence: 93%
“…In our previous research, we reported that HXNBR exhibited a high dielectric constant (14) and flexibility. 27 Additionally, Poikelispaä̈et al reported the high actuation performance of NBR rubbers. 2 This suggested that a DEA composed of HXNBR (having a high dielectric constant) and silica-coated BaTiO 3 particles can be applied to a high electric field, leading to high generated stress and strain.…”
Section: ■ Introductionmentioning
confidence: 99%